Comparison of Drug Discontinuation, Effectiveness, and Safety Between Clinical Trial Eligible and Ineligible Patients in BADBIR - Mason, Kayleigh J. (JAMA Dermatol, 2018)
IMPORTANCE: Patients with psoriasis enrolled in clinical trials of biologics may not be representative of the real-world population. There is evidence that patients ineligible for such trials have a greater risk of serious adverse events (SAEs), but the effect on drug discontinuation and effectiveness are unknown. OBJECTIVE: To determine whether (1) drug discontinuation, (2) effectiveness, and (3) rates of SAEs differ in patients with psoriasis categorized as eligible or ineligible for clinical trials. DESIGN, SETTING, AND PARTICIPANTS: An observational study using 157 dermatology centers in the United Kingdom and Republic of Ireland was carried out wherein we applied the eligibility criteria of clinical trials of biologic therapies for psoriasis to patients who were being followed up in the British Association of Dermatologists Biologic Interventions Register (BADBIR) and being prescribed biologics as part of standard clinical care. Patients with psoriasis registered to BADBIR who were taking etanercept (enbrel only; n = 1509), adalimumab (n = 4000), and ustekinumab (n = 1627) with at least 1 follow-up visit. Eligibility criteria were extracted from phase 3 licensing trials for etanercept, adalimumab, and ustekinumab for the treatment of moderate to severe psoriasis. Patients in BADBIR with a missing baseline Psoriasis Area and Severity Index (PASI) or baseline PASI value less than 10 (etanercept) or less than 12 (adalimumab; ustekinumab) but who would otherwise be eligible were investigated separately. Eligibility categories applied to BADBIR included: eligible, ineligible, insufficient baseline PASI only, and missing baseline PASI only. MAIN OUTCOMES AND MEASURES: (1) Drug discontinuation: cumulative incidence at 12 months by stop reason per eligibility category and drug; (2) effectiveness: linear regression of absolute change in PASI from baseline to 6 and 12 months; and (3) SAEs: incidence rate ratio (IRR) at 12 months between eligibility categories per drug. RESULTS: The mean (SD) age of the 7136 patients included in the analysis was 45 (13) years and 2924 (41%) were women and 4212 (59%) were men. Of 7136 patients, 839 (56%) etanercept, 2219 (56%) adalimumab, and 754 (46%) ustekinumab registrations were categorized as eligible. The most common reasons for ineligibility were diabetes (etanercept, 143 [9%]; ustekinumab, 201 [12%]) and nonchronic plaque psoriasis (adalimumab, 157 [4%]). Patients categorized as ineligible (etanercept, 367 [24%]; adalimumab, 282 [7%]; ustekinumab, 394 [24%]) achieved a smaller absolute change in PASI after 6 and 12 months (adalimumab, ustekinumab), and had significantly higher rates of SAEs compared with the eligible category (etanercept: IRR, 1.9; 95% CI, 1.4-2.6; adalimumab: IRR, 2.0; 95% CI, 1.5-2.6; ustekinumab: IRR, 2.8; 95% CI, 2.1-3.8). No significant differences in drug discontinuation were observed between categories. CONCLUSIONS AND RELEVANCE: Clinical trial effectiveness and safety outcomes are not representative of real-world patients in BADBIR patients categorized as ineligible for such trials.